The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/anie.201712644
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Dual‐Color Photon Upconversion: A Singlet‐to‐Triplet Absorption Sensitizer in a Soft Luminescent Cyclophane

Abstract: Reversible emission color switching of triplet-triplet annihilation-based photon upconversion (TTA-UC) is achieved by employing an Os complex sensitizer with singlet-to-triplet (S-T) absorption and an asymmetric luminescent cyclophane with switchable emission characteristics. The cyclophane contains the 9,10-bis(phenylethynyl)anthracene unit as an emitter and can assemble into two different structures, a stable crystalline phase and a metastable supercooled nematic phase. The two structures exhibit green and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…DSC measurements clarified the phase transition behavior of cyclophane 1 (Figure 3). A phase transition from isotropic to nematic was observed at 57.6 • C on cooling, and further cooling results in a glass transition at −15.1 • C. In contrast with unsymmetric cyclophanes investigated in our previous studies [23][24][25], no transitions to crystalline phases appear on the heating DSC traces. As shown in Figure 4, no clear peaks were observed in the X-ray diffraction pattern obtained from cyclophane 1 at r.t., which coincides with the fact that cyclophane 1 exhibits the nematic LC phase at r.t.…”
Section: Lc Propertiescontrasting
confidence: 62%
See 3 more Smart Citations
“…DSC measurements clarified the phase transition behavior of cyclophane 1 (Figure 3). A phase transition from isotropic to nematic was observed at 57.6 • C on cooling, and further cooling results in a glass transition at −15.1 • C. In contrast with unsymmetric cyclophanes investigated in our previous studies [23][24][25], no transitions to crystalline phases appear on the heating DSC traces. As shown in Figure 4, no clear peaks were observed in the X-ray diffraction pattern obtained from cyclophane 1 at r.t., which coincides with the fact that cyclophane 1 exhibits the nematic LC phase at r.t.…”
Section: Lc Propertiescontrasting
confidence: 62%
“…The course of our previous studies on luminescent cyclophanes [22][23][24][25][26][27][28][29] suggested that the introduction of a cyclic structure into luminophores is a promising way to achieve mechanoresponsive luminescent materials [3,4,[30][31][32][33][34][35][36]. Luminescent cyclophanes having longer spacers have been found to show nematic LC properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luminescent cyclophanes are intriguing compounds as they may exhibit unconventional photophysical functions that have never been achieved with the acyclic compounds. [10][11][12] The cyclic structure disturbs the ordered and close-molecular packing, which results in the formation of liquid-crystalline (LC) phases over wide temperature ranges. Even though a number of cyclophanes have been reported to show LC phases, 13,14 their luminescent properties remain unexplored.…”
Section: Introductionmentioning
confidence: 99%